Soil smoldering in temperate forests: a neglected contributor to fire carbon emissions revealed by atmospheric mixing ratios - L. Vallet; L. Vallet; C. Abdallah; T. Lauvaux; L. Joly; M. Ramonet; P. Ciais; M. Lopez; I. Xueref-Remy; F. Mouillot (Biogeosciences)
Fire is regarded as an essential climate variable, emitting greenhouse gases in the combustion process. Current global assessments of fire emissions traditionally rely on coarse remotely sensed burned-area data, along with biome-specific combustion completeness and emission factors (EFs). However, large uncertainties persist regarding burned areas, biomass affected, and emission factors. Recent increases in resolution have improved previous estimates of burned areas and aboveground biomass while increasing the information content used to derive emission factors, complemented by airborne sensors deployed in the tropics. To date, temperate forests, characterized by a lower fire incidence and stricter aerial surveillance restrictions near wildfires, have received less attention. In this study, we leveraged the distinctive fire season of 2022, which impacted western European temperate forests, to investigate fire emissions monitored by the atmospheric tower network. We examined the role of soil smoldering combustion responsible for higher carbon emissions, locally reported by firefighters but not accounted for in temperate fire emission budgets. We assessed the CO/CO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="45pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="356b6e8878f951fcbd552c4e835ac995"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-213-2025-ie00001.svg" width="45pt" height="14pt" src="bg-22-213-2025-ie00001.png"/></svg:svg> ratio released by major fires in the Mediterranean, Atlantic pine, and Atlantic temperate forests of France. Our findings revealed low modified combustion efficiency (MCE) for the two Atlantic temperate regions, supporting the assumption of heavy smoldering combustion. This type of combustion was associated with specific fire characteristics, such as long-lasting thermal fire signals, and affected ecosystems encompassing needle leaf species, peatlands, and superficial lignite deposits in the soils. Thanks to high-resolution data (approximately 10 m) on burned areas, tree biomass, peatlands, and soil organic matter (SOM), we proposed a revised combustion emission framework consistent with the observed MCEs. Our estimates revealed that 6.15 Mt CO2 (±2.65) was emitted, with belowground stock accounting for 51.75 % (±16.05). Additionally, we calculated a total emission of 1.14 Mt CO (±0.61), with 84.85 % (±3.75) originating from belowground combustion. As a result, the carbon emissions from the 2022 fires in France amounted to 7.95 MtCO2-eq (±3.62). These values exceed by 2-fold the Global Fire Assimilation System (GFAS) estimates for the country, reaching 4.18 MtCO2-eq (CO and CO2). Fires represent 1.97 % (±0.89) of the country's annual carbon footprint, corresponding to a reduction of 30 % in the forest carbon sink this year. Consequently, we conclude that current European fire emission estimates should be revised to account for soil combustion in temperate forests. We also recommend the use of atmospheric mixing ratios as an effective monitoring system of prolonged soil fires that have the potential to re-ignite in the following weeks.